2009
DOI: 10.2166/wh.2009.050
|View full text |Cite
|
Sign up to set email alerts
|

A study of the use and impacts of LifeStraw™ in a settlement camp in southern Gezira, Sudan

Abstract: A total of 647 eligible subjects participated in the study. Two week incidence of diarrhoeal rates were estimated by a community survey some four months before and again four months after provision of the LifeStrawY. In addition counts were kept of people attending at the community clinic with diarrhoea. Compliance rates were good with 86.5% of people saying they always used it and only 3.7% saying they had never used it. In a before implementation survey 15.3% of participants reported diarrhoea in the previou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 11 publications
0
23
0
Order By: Relevance
“…Many studies evaluating interventions to improve water and sanitation use a before and after study design with no control group [23][24][25]. Our study results demonstrated that this common approach risks overestimating the impact of interventions in a dynamic urban community.…”
Section: Discussionmentioning
confidence: 83%
“…Many studies evaluating interventions to improve water and sanitation use a before and after study design with no control group [23][24][25]. Our study results demonstrated that this common approach risks overestimating the impact of interventions in a dynamic urban community.…”
Section: Discussionmentioning
confidence: 83%
“…Some of these household interventions were undertaken with HIV-positive persons (26) and the elderly (25). Other household interventions were tested as personal filtration devices well-suited for natural disaster conditions (41). …”
Section: History Of Water Sanitation and Hygiene Researchmentioning
confidence: 99%
“…There is also a portable and efficient system for water purification -LifeStraw-, developed for field workers, who need to drink water from surface sources. In this study, Elsanousi et al [29] showed that participants who use the LifeStraw experienced minor events of diarrhea compared to whom did not use this device (15.3 vs. 2.3%).…”
Section: Detection Of Diarrheogenic Strains Of E Coli (Dec)mentioning
confidence: 57%